(untitled) (European Journal of Interdisciplinary Research and Development, 2026)
The convergence of digital transformation and escalating ecological crises presents both unprecedented challenges and opportunities for environmental education. This article examines the philosophical dimensions of developing ecological competence among youth through digital learning platforms, with particular attention to the Uzbek context. Drawing on critical theory of technology, posthumanist pedagogy, and decolonial perspectives, the analysis explores the ontological, epistemological, and axiological foundations of digitally-mediated environmental education. The article argues that while digital platforms offer significant potential for scaling environmental education and engaging digitally-native generations, they also embody fundamental philosophical tensions: the mediation of nature through screens, the risk of techno-solutionism, the tension between behavior modification and autonomous consciousness, and the potential marginalization of traditional ecological knowledge.